2015
DOI: 10.1074/jbc.m115.644385
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-independent Expression of Caenorhabditis elegans Antizyme

Abstract: Background: Ornithine decarboxylase degradation by the proteasome is promoted by antizyme. Results: A novel reporter gene approach was established to monitor translational frameshifting of C. elegans antizyme in vivo. Conclusion: Induction of antizyme-frameshifting also occurs under stressful conditions, even in the absence of polyamine synthesis and independent of polyamine concentrations. Significance: A polyamine-independent regulation of frameshifting under stressful conditions is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Agmatine has long been known to affect antizyme frameshifting ( 305 ) and antizyme influences uptake of the nitric oxide synthase inhibitor, agmatine, that has neurological significance ( 306 ). The influence of antizymes, both by direct binding and indirectly, on other pathways and the potential role of factors other than polyamines on antizyme frameshifting, is the subject of several reports and of active investigation ( 291 , 307 , 308 ). The potential for polyamine levels to have specific effects on other cases of frameshifting also needs to be kept in mind especially as a certain combination of the levels of putrescine and spermidine was shown to influence the S. cerevisiae mobile element Ty1 frameshifting and so the rate of its retrotransposition ( 309 ).…”
Section: Free Living Organism Chromosomal Genes Lacking Mobile Predecmentioning
confidence: 99%
“…Agmatine has long been known to affect antizyme frameshifting ( 305 ) and antizyme influences uptake of the nitric oxide synthase inhibitor, agmatine, that has neurological significance ( 306 ). The influence of antizymes, both by direct binding and indirectly, on other pathways and the potential role of factors other than polyamines on antizyme frameshifting, is the subject of several reports and of active investigation ( 291 , 307 , 308 ). The potential for polyamine levels to have specific effects on other cases of frameshifting also needs to be kept in mind especially as a certain combination of the levels of putrescine and spermidine was shown to influence the S. cerevisiae mobile element Ty1 frameshifting and so the rate of its retrotransposition ( 309 ).…”
Section: Free Living Organism Chromosomal Genes Lacking Mobile Predecmentioning
confidence: 99%
“…They are essential for cell proliferation, differentiation, and apoptosis [ 1 , 2 ], and function as anti-inflammatories, anti-oxidants, and free radical scavengers [ 3 - 5 ]. During the aging process, polyamines, especially spermidine (SPD), are depleted in the spleen, ovary, liver, stomach, lung, kidney, muscle, and thymus [ 6 , 7 ]. Stegehake, et al reported that cellular polyamine levels decreased in aging post-reproductive Caenorhabditis elegans [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the aging process, polyamines, especially spermidine (SPD), are depleted in the spleen, ovary, liver, stomach, lung, kidney, muscle, and thymus [ 6 , 7 ]. Stegehake, et al reported that cellular polyamine levels decreased in aging post-reproductive Caenorhabditis elegans [ 6 ]. Enot, et al found that polyamines are depleted by palmitate, but enhanced by oleate in mouse liver, heart, and skeletal muscle [ 7 ].…”
Section: Introductionmentioning
confidence: 99%